2017
DOI: 10.1021/acs.jcim.6b00454
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Evaluation of the Enantiomers of a Novel Adenylyl Cyclase 2 Inhibitor

Abstract: Adenylyl cyclase 2 (AC2) is one of nine membrane-bound isoforms of adenylyl cyclase that converts ATP into cyclic AMP (cAMP), an important second messenger molecule. Upregulation of AC2 is linked to cancers like pancreatic and small intestinal neuroendocrine tumors (NETs). The structures of the various isoforms of adenylyl cyclases are highly homologous, posing a significant challenge to drug discovery efforts for an effective, isoform-selective modulator of AC2. In a previous study, a screen identified a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…33,34,41,42 The EP-based strategy is becoming widely used in MD simulations of protein-ligand systems. [43][44][45][46] Some of these studies employed the MD trajectories in subsequent MM-PBSA 32,47 or MM-GBSA (Molecular Mechanics -Generalized-Born Surface Area) calculations [48][49][50][51] to estimate ∆G bind . Even though the MM/MD sampling is, in principle, more accurate in the presence of an EP, its impact on the accuracy of ∆G solv predictions is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…33,34,41,42 The EP-based strategy is becoming widely used in MD simulations of protein-ligand systems. [43][44][45][46] Some of these studies employed the MD trajectories in subsequent MM-PBSA 32,47 or MM-GBSA (Molecular Mechanics -Generalized-Born Surface Area) calculations [48][49][50][51] to estimate ∆G bind . Even though the MM/MD sampling is, in principle, more accurate in the presence of an EP, its impact on the accuracy of ∆G solv predictions is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…33,34,41,42 The EP-based strategy is becoming widely used in MD simulations of protein-ligand systems. [43][44][45][46] Some of these studies employed the MD trajectories in subsequent MM-PBSA 32,47 or MM-GBSA (Molecular Mechanics -Generalized-Born Surface Area) calculations [48][49][50][51] to estimate ∆G bind . Even though the MM/MD sampling is, in principle, more accurate in the presence of an EP, its impact on the accuracy of ∆G solv predictions is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the existence of phospholipid-halogen interactions, we carried out MM/MD simulations with a series of halobenzenes in a hydrated phospholipid (POPC) bilayer environment, using an extra-point (EP) approach to model the XB-properties of the halogenated species. [81][82][83][84] This methodology, that had been widely applied in the computational investigation of a variety of protein-ligand systems, [86][87][88][89]102,104,105 provided evidences supporting the role of XB interactions in lipid-ligand recognition events. Our results also showed that, similarly to other biological systems, 30,80 XBs In summary, the role of XB interactions in lipid-ligand systems was tackled for the first time and our data provide important insights into membrane-(halo)drug recognition mechanisms at the molecular level.…”
Section: Discussionmentioning
confidence: 99%